2018
DOI: 10.1108/srj-07-2017-0114
|View full text |Cite
|
Sign up to set email alerts
|

Corporate values from a personal perspective

Abstract: Purpose The paper aims to analyse organisational values from a personal perspective. The purpose was to explore how employees learn about corporate values and how they relate to these values. The motivation has been one of discovery of current practices in businesses, with a strong focus on corporate values and their effects on employees. Design/methodology/approach The authors offer a review of the key definitions and main theoretical frameworks of values. Four case studies provide empirical data to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…They are to be self-consolidated over time so that enterprises may keep being developed securely and sustainably; overcome never-ending conflicts, disputes and difficult situations; establish trust and credibility in the society and the local community with diverse partners. The standard system of values is to be consulted and shared as fundamentals forming individual values (Illes and Vogell, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are to be self-consolidated over time so that enterprises may keep being developed securely and sustainably; overcome never-ending conflicts, disputes and difficult situations; establish trust and credibility in the society and the local community with diverse partners. The standard system of values is to be consulted and shared as fundamentals forming individual values (Illes and Vogell, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For the enterprise to keep being sustainable and overcome serious conflicts and difficult situations, a corporate system of values should be settled and shared beyond the framework of individual values (McCoy, 1997; Illes and Vogell, 2018). This values system and the reliance on it will become the strongest motivation to integrate enterprise in all of its aspects to confront the potentially biggest conflicts and inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…The "2018 Deloitte Global Human Capital Trends" found that although 94% of respondents believe that "agility and collaboration" are critical for the future-orientation of the firm, only 17% of people will actively endorse change (Deloitte Insights, 2018). According to Illes and Vogell (2018), corporate values are often designed by top management regardless of the values attractive to their employees. Therefore, employees perceive values and norms quite different at the individual level.…”
Section: The Relationship Between Values and Individual Behaviormentioning
confidence: 99%
“…In the modern conditions of the development of a post-industrial society in the field of technical production, centralization is replaced by autonomy and the associated MATEC Web of Conferences 344, 01003 (2021) MPM 2021 https://doi.org/10.1051/matecconf/202134401003 responsibility [4,5]. In a post-industrial society, individualization is recognized as the main characteristic of human capital [6,7,8]. The inevitable transition to free and responsible activity of individuals is proved by the well-known researcher in the field of sociology and political science D. Bell [4].…”
Section: Introductionmentioning
confidence: 99%